Nicene Council: A Crucial Process in the Formation of Christian Doctrine - Agus Widodo (Fakultas Teologi, Universitas Sanata Dharma, 2025)
In 2025, the Church commemorates the 1700th anniversary of the Council of Nicaea, convened in 325. While the council is best known for formulating the Nicene Creed, the version commonly recited today was later refined at the Council of Constantinople and adapted for liturgical use. Beyond the Creed, the council also issued 20 canons addressing various aspects of ecclesiastical discipline. The Fathers of Nicaea did not create the Creed from scratch; rather, they articulated it based on the faith they had received, understood, and handed down to future generations. The same principle applied to the canons, which were rooted in inherited traditions rather than entirely new prescriptions. Thus, the Council of Nicaea should be seen as a crucial moment in shaping Christian doctrine – particularly concerning Christology and the Trinity – while also laying the foundation for ecclesiastical discipline. As an ongoing process, neither its doctrinal nor disciplinary outcomes were static or final; instead, they remained part of the Church’s living tradition, requiring continuous reception, interpretation, and adaptation over time. However, to ensure focus and depth, this discussion will specifically examine the Nicene Creed, exploring its biblical foundations, its early development in the teachings of the Church Fathers, and its enduring authority and reception in later periods.